Minimising the impact of infectious outbreaks on resident quality of life: A qualitative proof of concept study using the Adult Social Care Outcomes Toolkit (ASCOT) - Diane Bunn; Wenjing Zhang; Nick Smith; Oluseyi Jimoh; Jane Greenstock; Mohammud Edoo; Ann-Marie Towers (PLoS ONE, 2025)
Introduction Infection control measures (ICMs) used to mitigate the effects of infectious outbreaks in care homes impact on resident quality of life (QoL). This qualitative proof-of-concept study explored whether the Adult Social Care Outcomes Toolkit (ASCOT) could feasibly support care home staff in recognising and minimising these impacts. Methods There were two phases involving online interviews with six care home managers/deputies from five homes who had managed notifiable outbreak(s) in the previous six months in two regions of England. Phase 1, using an incident analysis approach, explored the impact of outbreaks and ICMs on resident QoL, mapping data to the eight ASCOT domains. Phase 2 assessed the usefulness of using ASCOT to identify, monitor and minimise impacts on resident QoL during infectious outbreaks. Follow-up interviews were conducted with four care homes from phase 1 and six healthcare professionals with ICM responsibilities. Online interviews were analysed using framework analysis. Findings Phase 1: three types of outbreaks (COVID-19, norovirus, chest infections) were discussed. All were managed using standard ICMs: isolation, increased cleaning, and staff wearing personal protection equipment. The impacts of these measures on resident QoL were described. Phase 2: two overarching themes identified: (i) ICMs as a personal cost for the greater good and (ii) the potential of ASCOT in minimising impacts of infectious outbreaks on resident QoL as a tool to support care planning and mitigating impacts. Conclusion ASCOT can support planning to mitigate the effects of ICMs for infectious outbreaks on resident QoL.